THE IMPORTANCE OF YOUTH'S INNOVATIVE THINKING IN THE DEVELOPMENT OF ARTIFICIAL INTELLIGENCE (Web of Teachers: Inderscience Research, 2026)
This article discusses the impact of artificial intelligence on human development today, as well as the importance and key aspects of youth's innovative thinking in the development of artificial intelligence.